Tafsir Nurul Qur'an: sebauah tafsir sederhana menuju cahaya Al Qur'an - Kamal Faqih-Imani (Al-Huda, 2005)
sn. Jil.1-10=c.1-3 ; jil.11, 19,20=c.1-4 / ir,ji.1-10,c.4-5 ; jil.11,19,20,c.5/tr, jil.5=c.6/nr,jil.16-17=c.1-2